2021
DOI: 10.7150/ijms.55274
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of Low intensity Extracorporeal Shock Wave Therapy (Li-ESWT) on diabetic bladder dysfunction in a rat model

Abstract: Objectives: Low intensity extracorporeal shock wave therapy (Li-ESWT) has proven to be effective and safe for the treatment of various urological disorders including erectile dysfunction and chronic pelvic pain syndrome. In this study, we elucidated the therapeutic effect and possible mechanisms of Li-ESWT on diabetic bladder dysfunction (DBD) in a rat model. Materials and Methods: In all, thirty-two female Sprague-Dawley rats were divided into three groups: normal control (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Moreover, this state appeared 1 week after the STZ injection and lasted 3 months. Currently, research on DBD is mostly carried out in the eighth week after the successful establishment of a diabetic rat model [ 40 , 41 ]. Therefore, in this study, STZ–HFD was selected to induce T2DM, and the evaluation was conducted after 8 weeks of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this state appeared 1 week after the STZ injection and lasted 3 months. Currently, research on DBD is mostly carried out in the eighth week after the successful establishment of a diabetic rat model [ 40 , 41 ]. Therefore, in this study, STZ–HFD was selected to induce T2DM, and the evaluation was conducted after 8 weeks of feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal and human studies have shown that LESW can be applied to treat several different bladder disorders by using therapeutic effects to increase vasculature, reduce inflammation, and facilitate reinnervation. LESW also ameliorates bladder dysfunction and urinary continence in a rat model of diabetic bladder dysfunction, and the results showed that LESW can restore the nerve expression of the urethra and the vascularization of the bladder [ 78 , 79 ]. In a cryoinjury-induced detrusor underactivity rat model, LESW was shown to improve the composition of the bladder wall and hasten functional recovery [ 80 ].…”
Section: Lesw Reduces Tissue Inflammation and Attenuates Pain And Bla...mentioning
confidence: 99%
“…Clinical application of LiESWT for various urological disorders, such as ED [32][33][34][35][36], IC/BPS [40], diabetes-induced underactive bladder [42,43], OAB [38], and SUI [39], have been recently explored. Gruenwald et al implied the efficacy of LiESWT in severe ED patients who respond poorly to PDE5i therapy and suggested that LiESWT significantly improved erectile rigidity and sexual satisfactions [44].…”
Section: Discussionmentioning
confidence: 99%